Recent Advances in Heat Pipes - Aly, Wael I. A. (IntechOpen, 2019)
Heat pipes are considered as an effective thermal solution, particularly in high heat flux applications and in situations where there is a combination of nonuniform heat loading, limited airflow over the heat-generating components, and space or weight constraints. This book is intended to explore some of the recent advances in heat pipes and their applications in thermal systems. The first chapter is an introductory chapter about the recent advances in heat pipes in general. The second chapter is about thermosyphon heat pipe technology; working principles, advantages, and disadvantages; application ranges; and using computational fluid dynamics in modeling thermosyphons. The third chapter is about recent research into loop heat pipes (LHPs). The last chapter presents a novel liquid-vapor separator-incorporated gravitational LHP.